Entrepreneurial education and social impacts business: a study on the Administration course of the State University of Santa Cruz, in Ilhéus, Bahia (Research, Society and Development, 2021)
The debate about entrepreneurial education and social impact business has gained emphasis in recent years. They are seen as a means to develop techniques and alternatives to add values both in the economic and social spheres. This article aims to analyze the practice of disseminating knowledge about entrepreneurship, social entrepreneurship and social impact businesses in the UESC administration course, making a comparative analysis between the curriculum of the UESC administration course versus the UESC administration course. University of São Paulo (USP), and finally an analysis of the curricular pedagogical project (PPC) with the assistance of the coordinator of the department of the UESC administration course. Thus, this research is predominantly qualitative, with the design of bibliographic, documentary and empirical research. It was possible to observe that there is a fragile relationship between disciplines focused on entrepreneurial education and business with social impacts in the curriculum of the Administration course at the State University of Santa Cruz. According to the analyzes made in the PPC and in the system of disciplines aimed at entrepreneurial education and social impact businesses, there are no specific disciplines for the theme, but some that can be considered as assistants in the new process. Among the conclusions, the importance of teaching engagement and alignment of teaching, research and extension processes is emphasized so that entrepreneurial education for impact businesses is effective in training administrators, based on the Principles for Responsible Education and Management, proposed by the UN in 2007.